Evaluation of the effectiveness of antiparasitic in sheep from the Experimental Unama Farm, Santarém-PA (Research, Society and Development, 2021)
This study aimed to evaluate the effectiveness of the antiparasitic drugs Albendazol and Levamizol in naturally infected sheep at the Experimental Farm at Unama. Twenty-two animals were used, divided into three groups: four control animals (untreated); nine treated with Albendazole; and nine treated with Levamizol. Pre-treatment and post-treatment evaluation was performed (0th, 14th day) and, after counting eggs per gram of feces, the percentage reduction (RCOF) was calculated. It was observed that sheep treated with Albendazol had low effectiveness on the 14th day, reaching a RCOF of 10%. In the group treated with Levamizol, the RCOF was 70% on the 14th day. It is concluded that antiparasitic drugs were not effective in the treatment, demonstrating that other measures must be included in the management of animals, in addition to periodic evaluation through the examination of feces to verify the effectiveness of the drugs.